Pengaruh Biaya Operasional, Perputaran Persediaan, dan Debt to Equity Ratio terhadap Profitabilitas (Studi Pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Arvita, Rizki; Novita, Mega Darmi; Wibisono, Kasman; Syafitri, Hany Nur Kayla (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the effect of operating costs, inventory turnover, and debt to equity ratio on the profitability of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The independent variables in this study are operational costs, inventory turnover, and debt to equity ratio, while the independent variable is profitability. This study uses secondary data in the form of company financial reports. This study used a purposive sampling technique to obtain 8 samples from a total population of 11 companies. Multiple linear regression analysis was used for data analysis in this study. The results of the partial test that (1) operational costs have no significant effect on profitability with a tcount < ttable -0.086 <2.028 and a significance value of 0.932 > 0.05 (2) inventory turnover has a significant positive effect on profitability with a tcount < ttable 3.451 > 2.028 and a significance value of 0.001 <0.05 (3) the debt to equity ratio has a significant negative effect on profitability with a tcount < ttable 6.415 > 2.028 and a significance value of 0.00 <0.05. Meanwhile, the simultaneous test results of operational costs, inventory turnover, and debt to equity ratio have a significant effect on profitability with Fcount > Ftable 18.596 > 2.866 and a significance value of 0.00 <0.05.Keywords: Operational Costs, Inventory Turnover, Debt to Equity Ratio, and Profitability